PENGARUH GENDER DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR SCOOPY (Studi Kasus Pada Desa Mekar Sari Kecamatan Laut Tador) - Tika Ardhana; Sintia Amelia Saragih; Dedy Dwi Arseto; Indra Welly Arifin (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the influence of Gender and Product Design on Purchase Decisions of Scoopy motorcycles in Mekar Sari Village. The research method used is a quantitative approach with SmartPLS version 3.0. Questionnaires were distributed to 96 respondents. The data analysis methods used in this study include the measurement model (outer model), which consists of validity and reliability tests, and the structural model (inner model), which includes the coefficient of determination (r²) and hypothesis testing using the t-test and f-test (simultaneous test). The results from SmartPLS 3.0 in this study indicate that: Gender influences the purchase decision of Scoopy motorcycles in Mekar Sari Village. Design influences the purchase decision of Scoopy motorcycles in Mekar Sari Village. Gender and product design both influence the purchase decision of Scoopy motorcycles in Mekar Sari Village.